Effects of Varying CDS Levels and Drying and Cooling Temperatures on Flowability Properties of DDGS - Rosentrater, Kurt A.; Muthukumarappan, K.; Bhadra, Rumela (My University, 2013)
Demand for alternative fuels and the need to reduce dependence on fossil fuels have triggered the growth of corn-based ethanol production, which is expected to rise in future years. Transportation of the coproduct distillers dried grains with solubles (DDGS) from this industry occurs under various environmental conditions. Transporting DDGS is often problematic, because caking between the particles can lead to flow problems. In this study, we have prepared DDGS by combining condensed distillers solubles (CDS) with distillers wet grains and then drying. We investigated the effects of CDS level (10, 15, and 20%, wb), drying temperature (100, 200, and 300°C), and cooling temperature (–12, 25, and 35°C) on the flowability of the resulting DDGS. Statistical analyses of the resulting data found significant differences among the cooling temperature levels for angle of repose, total flow and flood indices, dispersibility, water activity, and protein dispersibility index. Additionally, significant interaction effects between CDS, drying temperature, and cooling temperature levels for angle of repose, total flow and flood indices, dispersibility, and protein dispersibility index were observed. Response surface regression on selected dimensionless flowability parameters was also applied. However, multivariate PLS regression yielded better results (R² > 0.8) than response surface plots. Understanding the effects of drying and cooling temperatures as well as CDS levels can be used to help improve the industrial processing of DDGS and improve storage and transportation.
Keywords: Varying CDS Levels; Condensed distillers solubles (CDS); Drying temperatures; Cooling temperatures; Flowability properties; Distillers dried grains with solubles (DDGS)